Measurement of Deby length By using single probe technique - Salman, Emad A. (University of Thi-Qar Journal of Science, 2014)
In this work the planer magnetron sputtering device was used. As well as a 1mm copper diameter and 3 mm length Langmuir probe was used a diagnostic device to investigate electron temperature, electron density and Deby length under different pressure at distance 0.7 cm from the anode surface was measured.The effect of the pressure on plasma parameter was studied at this distance.The result of this work shown that, when the pressure increased the electron temperature and Deby length will decreased while the electron density increased